Daily variability of California coastal low cloudiness: A balancing act between stability and subsidence. Issue 7 (1st April 2017) - Clemesha, Rachel E. S.; Gershunov, Alexander; Iacobellis, Sam F.; Cayan, Daniel R.
Abstract: We examine mechanisms driving daily variability of summer coastal low cloudiness (CLC) along the California coast. Daily CLC is derived from a satellite record from 1996 to 2014. Atmospheric rather than oceanic processes are mostly responsible for daily fluctuations in vertical stability that dictate short‐period variation in CLC structure. Daily CLC anomalies are most strongly correlated to lower tropospheric stability anomalies to the north. The spatially offset nature of the cloud‐stability relationship is a result of the balancing act that affects low cloudiness wherein subsidence drives increased stability, which promotes cloudiness, but too much subsidence limits cloudiness. Lay explanations claim that high inland temperatures "pull in" CLC, but such a process presumably would have the high temperatures directly inland. Rather, we find that the spatially offset associations between CLC and atmospheric circulation result in positive correlations between CLC and inland surface temperature anomalies to the north. Key Points: Low cloud variability along the California coast is linked to stability and temperatures to the north Anomalously strong local subsidence reduces coastal low cloudiness (CLC) A set of CLC‐stability‐subsidence correlations indicate dynamic teleconnections